Multicultural Islamic Education in Modern Islamic Boarding Schools: The Integration of Islamic and Cultural Values - Fitria Luthfitasari; Imam Syafi’i (Vifada Journal of Education, 2026)
Islamic educational institutions play a strategic role in promoting multicultural educational values, particularly in modern Islamic boarding schools. This article analyzes the model of multicultural Islamic education at the Al-Muhibbin 4 Bahasa Modern Islamic Boarding School in Jatirogo, Tuban, with a primary focus on the integration of Islamic values and cultural arts. The research employs a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation of learning practices, dormitory life, language immersion, and the pesantren’s arts and cultural activities. Data analysis was conducted through data condensation, data presentation, and the derivation and verification of conclusions. The results of the study indicate that multicultural education at the pesantren is not only taught through tolerance-based curriculum but is also shaped by an educational ecosystem that encompasses classrooms, mosques, dormitories, student organizations, four-language instruction, wayang performances, karawitan, religious music, cultural parades, and drama. The main finding of this article is the Textual-Cultural Integration model, an educational model that connects the Qur’an, hadith, ethics, fiqh, and Islamic scholarly traditions with cultural realities through integrative pedagogy. The novelty of this article lies in the expansion of the Integrated Twin Towers paradigm from the relationship between religious and general knowledge to the relationship between Islamic texts and cultural contexts. This model contributes to the development of modern Islamic boarding schools that are religious, moderate, creative, and culturally aware.